Role of toll-like receptor signaling pathway in a rat model of spinal cord injury: a transcriptomic analysis - D'Angiolini, Simone; Trubiani, Oriana; Mazzon, Emanuela (Italian Journal of Anatomy and Embryology, 2023)
Spinal cord injury (SCI) is a debilitating condition characterized by primary and secondary damage to the spinal cord tissue encompassing the site of injury. In this study, we analyzed transcriptomic data from Rattus norvegicus with SCI induced by aneurysm clip impact-compression at seventh thoracic vertebra to explore the main alterations in pathways expression. RNA was extracted from the specific SCI region after 2 weeks and hybridized on Affymetrix GeneChip arrays. Differential gene expression analysis identified 5213 DEGs among which 25 showing a fold change < -2 or > 2. Over-representation analysis was performed using the 25 DEGs above mentioned and revealed the toll-like receptor (TLR) signaling pathway signaling pathway (rno04620) as the only significantly enriched pathway (q-value < 0.05). Further examination of the regulation of this pathway unveiled upregulation of MyD88, Tlr2, and Tlr4, activating NF-κB and MAPK pathways, leading to proinflammatory cytokine synthesis and cellular apoptosis. Upregulation of Cd80 and Cd86 indicated T-cell activation, while IFN-β downstream regulation showed increased expression of JAK-STAT signaling pathway genes. This transcriptomic perspective highlights the dysregulation of the TLR signaling pathway in SCI at 2 weeks and emphasizes its potential role in the pathology.